Sobre viagem: palmilhar limites, entrever transformações - Júlia Fonseca de Castro (2019)
What is known about traveling is the result of discourses that have centralized the meaning of the action of traveling, shaping the conceptual and imaginary fields related to it. Traveling, a largely diffused narrative construct integrated to the oral and written traditions, is a product of the language and thinking that are associated to projects of power and territory domination. This dissertation is a space for thinking and questioning this, it tracks the limits of the dominating traveling discourse, and foresees definitions, created by other subjects through other practices, which were distanced, for some unclear reason, from what has been commonly defined as traveling. It is a creative study that sees through narrative texts about the act of traveling to identify aspects of the discourse monopoly, but also the possibility of reinventing the dominant discourse. The reflexive essence of the research revisits traveling on the inside, in order to highlight the traveler’s necessity to understand herself completely so as to build a place of lucid expression and transformation, which may overcome the individualism and consumerism currently associated to traveling. Such place of expression can be described through the questioning of the idea of the traveler as a universal being, whose centralizing eye allows for an authoritarian and self-centered perspective. The historical asymmetry in discourse, which has moved the traveler’s eyesight from the outside to the inside, needs to be rebuilt through the appropriation of the platform for defining traveling. The narrative is a type of creative borrowing that entails several paths of creating a text, which enables imagining oneself in the place of other, allowing for understanding our own perspective through knowing the other’s place, landscape, culture, and people. Columns, essays, and literary texts were all considered from the same perspective to encourage debate about the essence of the mainstream western discourse about traveling. The interpretation and writing of texts on traveling aimed at underscoring meanings given by the traveler, as that of a witness, and also contemplative, Eurocentric, knowing, and masculine. Gonçalo Cadilhe, Raquel Ochoa, Jonathan Swift, Ítalo Calvino, Jorge Luis Borges, Tiago Salazar, Mário de Andrade, Guimarães Rosa: are some of the authors whose texts were read, allowing for deeper reflection. The research’s conclusion highlights the need of the narrative as a process for encouraging people towards having meaning in traveling, a no less important action than that of physically dislocating oneself. We conclude that it is necessary to increase the references that may help realize the subversive and transformative potentials in the act of traveling.